A Pilot Examination of the Use of Narrative Therapy With Individuals Diagnosed With PTSD. Issue 6 (10th November 2014) - Erbes, Christopher R.; Stillman, John R.; Wieling, Elizabeth; Bera, Walter; Leskela, Jennie
Abstract : Narrative therapy is a postmodern, collaborative therapy approach based on the elaboration of personal narratives for lived experiences. Many aspects of narrative therapy suggest it may have great potential for helping people who are negatively affected by traumatic experiences, including those diagnosed with posttraumatic stress disorder (PTSD). The potential notwithstanding, narrative therapy is relatively untested in any population, and has yet to receive empirical support for treatment among survivors of trauma. A pilot investigation of the use of narrative therapy with 14 veterans with a diagnosis of PTSD (11 treatment completers) is described. Participants completed structured diagnostic interviews and self‐report assessments of symptoms prior to and following 11 to 12 sessions of narrative therapy. After treatment, 3 of 11 treatment completers no longer met criteria for PTSD and 7 of 11 had clinically significant decreases in PTSD symptoms as measured by the Clinician Administered PTSD Scale. Pre‐ to posttreatment effect sizes on outcomes ranged from 0.57 to 0.88. These preliminary results, in conjunction with low rates of treatment dropout (21.4%) and a high level of reported satisfaction with the treatment, suggest that further study of narrative therapy is warranted as a potential alternative to existing treatments for PTSD.